Pengaruh CR, TAT, LTDER, dan Ukuran Perusahaan Terhadap Pertumbuhan Laba Perusahaan Sektor Industri Retail yang Terdaftar di BEI (2019-2022) - Hijr Widya Pangestu; Sri Sudarsi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the impact of the Current Ratio, Total Asset Turnover, Long-Term Debt to Equity, and Company Size on profit growth in retail sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2022 period. The data used were obtained from financial statements accessed through the IDX website. This research employs purposive sampling method. The data were analyzed using Multiple Linear Regression. The results show that Company Size has a positive and significant effect on profit growth, while the Current Ratio and Total Asset Turnover have no effect on profit growth, and Long-Term Debt to Equity has a negative and significant effect on profit growth.